Time-Poor, Working, Super-Rich - Giacomo Corneo (Institute of Labor Economics (IZA), 2017)
This paper revisits the standard model of labor supply under two additional assumptions: consumption requires time and some limited amount of work is enjoyable. Whereas introducing each assumption without the other one does not produce novel insights, combining them together does if the wage rate is sufficiently high. For top earners, work has a positive marginal utility at the optimum and above a critical wage level it converts into a pure consumption good. Their labor-supply curve is first backward bending and then vertical. This can justify an optimal marginal tax rate on top incomes equal to 100 percent. Top earners in the vertical half-line of the labor-supply curve optimally refrain from spending their entire income. At the macroeconomic level, this can generate a lack of effective demand. With some qualifications, these findings carry over to models that include savings and philanthropy.
Keywords: J22; H21; H24; 330; super-rich; labor supply; time allocation; effective demand; optimal taxation of top labor incomes